An In vitro Tuberculosis Granuloma Model in M. tuberculosis H37Rv: In vitro Tuberculosis Granuloma Model in M. tuberculosis H37Rv - Talita Shofa Adestia (Jurnal Biosains Pascasarjana, 2023)
M. tuberculosis is a bacterium that has many evasion mechanisms against the immune system, one of them is the formation of granulomas which is beneficial for the bacteria's survival. The granuloma structure is useful for limiting the spread of M. tuberculosis and localizing infection, also considered as part of M. tuberculosis life cycle that successful fighting the body's immune system. This study aims to look at the formation of an in vitro tuberculous granuloma model. This study used the True Experiment type which began with blood sampling, PBMC isolation, macrophage isolation, MOI 10 making and granulomas making. Granulomas were observed on day 0, 1, 4, 7, 9, 10 and 14. Cells started to aggress on day 1 and giant cells were seen on day 4. The granuloma formed on day 9 and was maintained on day 10, however, the granuloma ruptured on day 14 which caused the cells to re-aggregate. Keywords: Granuloma, M. tuberculosis, PBMC